Implementasi Proyek Penguatan Profil Pelajar Pancasila melalui Program 4 C’s On The Spot di SMP Khadijah Surabaya: Sebuah Pendekatan Multidisipliner - Muntafi’ah, Mas Umi; Kurnia PS, Alaika M. Bagus; Khoirunisa, Amelia (IAIN Pontianak, 2024)
The aim of this research is to examine multidisciplinary scientific learning at Khadijah Middle School in Surabaya as an alternative to the national exam which has been abolished. This research uses field research, in the form of phenomenology. The data sources obtained came from interviews, observation and documentation. So the conclusion of this research is that multidisciplinary learning projects from the 7 (seven) selected subjects can provide their own color to the students' perspective, so that they are able to provide a cooperative, respectful, responsible character and produce quality decisions.